Efeito do treino de discriminação simples sobre o repertório de pareamento ao modelo por identidade de um macaco-prego (Cebus apella) - MAN, Tiago Sales Larroudé de (2007)
this paper reports an experiment training to verify the function of simple simultaneous discrimination training with pairs of stimuli on identity match-to-sample performance with the same stimuli. An infant capuchin monkey with experience with identity match-to-sample served as subject. It was investigated how much training with a Repeated Shift of Simple Discrimination (RSSD) procedure would facilitate performance in match-to-sample with the same stimuli. Response ratio to advance the procedure and duration of the intertrial interval (ITI) were manipulated, and discriminative training for all possible pairs of a four-stimulus set was undergone. Identity match-to-sample with set A was used as baseline. Set B was trained in simple discrimination and tested in identity matching-to-sample. Test trials were interspersed among baseline trials. Correct responses were followed by a grape-flavor sugar pellet of 45 mg, and started the ITI. Incorrect responses ended the trial and started the ITI. Results shows variable performances on identity tests and RSSD, indicating small contribution of RSSD to IDMTS when to choices are used in both. Discuss about wrong patterns on identity test yelded by contraditory Stimulus Topography Control selectioned by RSSD procedure.